(untitled) (Italian Journal of Public Health, 2008)
Background: Environmental health studies often deal with health problems that are influenced by factors with a strong spatial component. However, most analyses of routinely collected health data (cancer register, medication data etc.) are performed at a spatially higher aggregated level. Analyses based on administrative units are frequently subject to confounding by different exposures or other factors and therefore possible effects may remain uncovered or effect estimates distorted. Methods: A medication prevalence study in the Tyrolean Wipptal, is presented as example for an address based analysis of public health data. To assess whether road or rail exposure is associated with the prescription of medicines the study population was divided in subgroups based on traffic source exposure levels at each address (exposure groups). The medication prevalence proportion for each exposure group was estimated using health insurance data. Results: Significant differences in medication for various exposure groups could be found. Mainly the railway and main road exposure groups showed higher medication prevalence in some age and medication groups. Conclusions: Address based spatial analysis of health register data is still an underutilized Public health technique. A persistent problem is the availability of important covariates (education, income etc.) on a more detailed level than municipalities. This situation might be improved if national statistics agencies provide such statistical data on the basis of the European wide raster system.